Faktor-faktor Yang Memengaruhi Pengelolaan Sampah Pada Sekolah Dasar di Kabupaten Bantul - Cahyani, Dwi Endah; Rahmi, Dwita Hadi (Jurnal Riset Daerah, 2021)
The waste problem is a problem faced by various regions in Indonesia, including Bantul Regency, ranging from the lack of public awareness, waste that is thrown carelessly on vacant land and in rivers, to landfills that have exceeded capacity. Previous research has been carried out on a community and community scale, but it is still rare to see from the perspective of the role of the world of education in handling waste problems. This is the background for the implementation of this research. This research was conducted with the aim of identifying the waste management system implemented in elementary schools in Bantul Regency and finding factors that influence waste management in elementary schools in Bantul Regency. The method used in this study is a qualitative deductive method. Methods of collecting data were interviews, questionnaires, observation, and documentation. The study was conducted at 14 elementary schools in Bantul Regency in both rural and urban areas. This research uses descriptive qualitative data processing and analysis methods. Testing the validity of the data in this study was carried out by triangulation. From the results of the study, it was found that most elementary schools in Bantul Regency had tried to implement a waste management system in accordance with government policies but still needed improvements in several ways. Waste management in elementary schools in Bantul Regency is influenced by factors such as school environmental conditions, availability of infrastructure, human resources, and funding/financing.